Станки с программным управлением, автоматические линии и агрегатные станки (Серия С-1 "Станкостроение", 1968)
Экземпляры: КХ (20240725) / Инвентарный номер: 457435 / Сис.шифр: 621.9 / Авт.знак: М 43 / ГРНТИ: 53 / ББК: 34